New hybrid bromopyridine-chalcones as in vivo phase II enzyme inducers: potential chemopreventive agents12. Issue 12 (20th October 2016) - Cabrera, Mauricio; Cerecetto, Hugo; González, Mercedes
Abstract : We report the synthesis of eighteen new potential cancer chemopreventive agents, structurally designed to combine (naphtho)chalcone and (bromo)pyridine skeletons. Abstract : Cancer prevention can be achieved by the administration of cancer chemopreventive agents (CCAs) that prevent, delay or reverse the carcinogenic process. CCAs that are able to induce detoxification enzymes, especially monofunctional phase II enzymes, have become an excellent therapeutic strategy. Herein, we report the synthesis of eighteen new potential CCAs, structurally designed to combine (naphtho)chalcone and (bromo)pyridine skeletons. After a selection process involving in vitro phase II induction studies, cytotoxicity against tumoral cells, mutagenicity (the Ames test), and capability for DNA strand breakage (the alkaline comet assay), compound22, ( E )-3-(2-bromopyridin-3-yl)-1-(2-hydroxyphenyl)-2-propen-1-one, was selected for animal studies. The in vivo proof of concept study for derivative22 demonstrated that it was able to significantly increase the QR and GST activities in the liver, colon and mammary gland without significant induction of the phase I enzyme, CYP. Additionally, we found that for22 and another in vitro QR activity inducer, ( E )-1-(2-hydroxyphenyl)-3-(naphthalen-1-yl)-2-propen-1-one (compound8 ), Nrf2 nuclear translocation is operative allowing the exertion of protective effects via the expression of downstream phase II enzymes.